Steam reforming of dimethyl ether promoted by surface protonics in an electric field. (2nd August 2018) - Inagaki, Reona; Manabe, Ryo; Hisai, Yudai; Kamite, Yukiko; Yabe, Tomohiro; Ogo, Shuhei; Sekine, Yasushi
Abstract: The catalytic steam reforming of dimethyl ether (DME) in an electric field was carried out and the effects of proton hopping induced by the electric field on a Pd-supported CeO2 catalyst surface were investigated. The hydrolysis of DME was promoted even on Pd/CeO2 catalyst by the application of the electric field at low temperatures (in the range of 423–623 K), while the direct decomposition of DME was suppressed. The apparent activation energy in this temperature range was much lower with (17.2 kJ mol −1 ) than without (79.0 kJ mol −1 ) the electric field. Kinetic analyses demonstrated that the effect of the reactant partial pressures was also markedly different with and without the electric field. The effect of the partial pressure of water and electrochemical impedance spectra strongly suggest that surface proton hopping promotes the steam reforming of DME in an electric field at low temperatures. Graphical abstract: Image 1 Highlights: Catalytic steam reforming of dimethyl ether (DME) in an electric field was investigated. Hydrolysis of DME was promoted while the direct decomposition of DME was suppressed by the application of the electric field. Apparent activation energy was much lower with (17.2 kJ mol −1 ) than without (79.0 kJ mol −1 ) the electric field. Electrochemical impedance spectra strongly suggest that surface proton hopping promotes the steam reforming of DME.